The Influence of Social Media Marketing on Brand Loyalty through Brand Trust and Brand Equity: A Study on Consumers of PT Blue Bird Tbk - Airlangga, Muhammad Yusuf; Wahyudi, Lilik (Universitas Muhammadiyah Pontianak, 2025)
This study examines the impact of Social Media Marketing (SMM) on Brand Loyalty, mediated by Brand Trust and Brand Equity, across two different social media platforms: TikTok (video-based) and Instagram (photo-based). A total of 450 respondents who had interacted with PT Bluebird's social media were surveyed using a structured questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the relationships among variables. The findings indicate that SMM significantly influences Brand Trust and Brand Equity, which in turn positively affect Brand Loyalty. Mediation analysis reveals that both Brand Trust and Brand Equity partially mediate the relationship between SMM and Brand Loyalty, with Brand Trust playing a more dominant role. Furthermore, TikTok demonstrates stronger path coefficients compared to Instagram, suggesting that video-based content fosters greater emotional engagement and trust. The study contributes both theoretically and practically by highlighting the importance of emotionally resonant content and platform-specific strategies in fostering long-term consumer loyalty.